Significance, Distribution, Biology and Varieties of Sesame Cultivated in Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance of the topic and usage. Sesame is one of the main oil crops grown in Uzbekistan since ancient times. It ranks first among oil crops in terms of the amount of oil contained in its seeds. Cold-pressed sesame is equal to olive oil in taste. Sesame seeds are used in the confectionery industry, in medicine, and also in the preparation of preserves. It is used in the preparation of candies, oriental sweets, various halwa, bakery products. Vegetable oil obtained by hot pressing is used for technical purposes, and it is burned to make a high-quality dream.